2020
DOI: 10.1002/cncy.22281
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic and histologic samples from patients infected by the novel coronavirus 2019 SARS‐CoV‐2: An Italian institutional experience focusing on biosafety procedures

Abstract: The 2019 coronavirus pandemic, which started in Wuhan, China, spread around the globe with dramatic and lethal effects.From the initial Chinese epicenter, the European diaspora taxed the resources of several countries and especially those of Italy, which was forced into a complete social and economic shutdown. Infection by droplets contaminating hands and surfaces represents the main vehicle of diffusion of the virus. The common and strong efforts to contain the pandemic have relevant effects on the management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 9 publications
0
49
0
4
Order By: Relevance
“…Children under the age of 9 have a mild course in nearly all cases although a new kind of disease entity during the COVID-19 period has been observed which resembles Kawasaki disease [24] . Postmortem research revealed that tissue responses to SARS-CoV-2 infection are distinct in different organs [25] , [26] . In comparison with observations made during the SARS-CoV-1 and MERS outbreaks, SARS-CoV-2 has similarities in risk group spread, but the case fatality rate of SARS-CoV-2 appears to be lower [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Children under the age of 9 have a mild course in nearly all cases although a new kind of disease entity during the COVID-19 period has been observed which resembles Kawasaki disease [24] . Postmortem research revealed that tissue responses to SARS-CoV-2 infection are distinct in different organs [25] , [26] . In comparison with observations made during the SARS-CoV-1 and MERS outbreaks, SARS-CoV-2 has similarities in risk group spread, but the case fatality rate of SARS-CoV-2 appears to be lower [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, another study revealed that formalin and glutaraldehyde can deactivate SARS-CoV depending on the temperature and time [9] . Rossi et al, [33] also recommend that histological tissues should stay for extended periods of formaldehyde fixation. On the contrary, Odega et al, [34] kicked against performing frozen sections on suspected coronavirus tissues except such a laboratory is assertive of restraining aerosols in the cryostat.…”
Section: Coronavirus Disease 2019 (Covid-19) and Sourcing Of Cadaversmentioning
confidence: 99%
“…Infection by droplets contaminating hands and surfaces are the foremost means of dispersal of the virus [29]. GI tract is also a plausible spreading pathway and target organ of SARS-CoV-2 [30].…”
Section: Transmissionmentioning
confidence: 99%